Magnetic Nanoparticles A Study by Synchrotron Radiation and RF Transverse Susceptibility - Figueroa, Adriana I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Magnetic nanoparticles (NPs) are finding their place in many modern technologies such as electronics (memory or spintronic devices) and medicine (contrast media, electromagnetic thermal therapy) to name just a few examples. The application of modern techniques based on synchrotron radiation, in particular X-ray spectroscopies, as well as an rf transverse susceptibility probe, built ad hoc, allowed the author to investigate several classes of magnetic NPs with diverse applications. For example, the interesting anisotropic properties of CoW and CoPt NPs revealed new magnetic behaviour and phases. Gold NPs prepared on a biological template from Sulfolobus acidocaldarius S-layer, were shown to possess intrinsic magnetism caused by the electron exchange with the sulfur atoms of the template. Silica and oleic acid coated magnetite NPs showed excellent human compatibility while preserving the bulk magnetic figures of merit. Both macroscopic and microscopic properties of all these NPs, hitherto unexplained, have been revealed for the first time.
Introduction -- Experimental Techniques -- Structural and Magnetic Properties of Amorphous Co-W Alloyed Nanoparticles -- Breakdown of Hund's Third Rule in Amorphous Co-W Alloy Nanoparticles -- Structural and Magnetic Properties of Co-Pt Nanoparticles -- d-band Magnetism of Ag, Au, Pd and Pt Nanostructured Materials -- Transverse Susceptibility Measurement System for the PPMS -- Transverse Susceptibility of Iron Oxide Nanoparticles Systems -- General Conclusions.
Keywords: Magnetism; Magnetic materials; Nanotechnology; Metals; Nanoscale science; Nanoscience; Nanostructures; Magnetism, Magnetic Materials; Nanotechnology; Metallic Materials; Nanoscale Science and Technology